Production Of The Nucleocapsid Protein Of A Swine Nipah Virus Isolate In Escherichia Coli - Ong, Swee Tin (2002)
Nipah virus (NiV) possesses a nonsegmented, single-stranded negative sense RNA genome that contains six structural genes arranged in the order of 3' N-P-M-F-G-L 5'. The nucleocapsid (N) gene of Nipah virus isolated from swine was amplified from the viral RNA by reverse transcription polymerase chain reaction (RT-PCR). The nucleocapsid (N) gene of Nipah virus was cloned into the bacterial expression vector, pTrcHis2, for intracellular expression in three Escherichia coli strains: TOP 10, BL 21 and SG 935. The N protein was expressed as a 63 kDa fusion protein containing the myc epitope and His-tag at its C-terminal end. The amount of the fusion protein expressed in strain SG 935 was significantly higher than the other two strains, and was detected by the anti-myc antibody, anti-His and swine anti-NiV serum. The N gene sequence shared 99% homology with that of Nipah virus isolated from human. The coding region of N protein of NiV was cloned into different vectors and subsequently introduced into different E. coli strains. The yield of the N protein produced in different vectors and different hosts was compared. It was found that the amount of N protein expressed by the pTrcHis2 vector containing the trc promoter in E. coli SG 935 was four-fold higher than that of vector pRSETB and pGEX-4T-l in E. coli strain BL 21 series. Deletion of the N- or/and C-terminal region of the N protein revealed that the N-terminal region plays a role in N protein solubility, but a mutant (MN50fus) containing the second half of the N protein showed the highest expression level in all the three E. coli strains. Lowering the growth temperature of E. coli cell cultures to 25°C improved the solubility of the full-length and truncated Nfus protein from 50% to 80%. This study addresses the fundamental problems encountered in production of Nipah viral N protein in E. coli which may be useful as an alternative antigen for the detection of anti-NiV in swine.